Pengaruh Penerapan Indikator Mutu Layanan Klinis Bagian Rekam Medis terhadap Kepuasan Pasien di Puskesmas Gambut - Ni Wayan Kurnia Widya Wati; Sugeng Riyanto; Raden Yosep Eka Hendrawan (Jurnal Kesehatan Indonesia, 2020)
Patient satisfaction is a level of patient feeling that arises as a result of the performance of the health service obtained after the patient compares it to what he or she expects. The positive impact of clinical service quality indicators in the medical record section on patient satisfaction shows the level of perfection of patient satisfaction. Health is causing complacency in each patient. The purpose of this study is to find out the effect of the application of Clinical Service Quality Indicators in the Medical Records Section to Patient Satisfaction at Puskesmas Gambut. This research method uses a cross-sectional study. The results of this study obtained the achievement of clinical service quality indicators, namely the accuracy of patient identification is mostly in accordance with the standards of 42 documents medical record (84%) and the provision of < 10 minutes mostly according to the standard of 44 documents medical record (88%). The achievement of patient satisfaction is mostly very satisfied as many as 30 patients (60%). There is an effect of applying clinical service quality indicators (1. Precision patient identification, 2. Provision of documents less than 10 minutes) in the medical record section of patient satisfaction, namely the accuracy of patient identification of asimp. Sig 0.000 and the provision of < 10 minutes asimp. Sig 0.000.